AXIAL CAPACITY OF PILES BASED ON STATIC FORMULA STATIC LOADING AND PDA TEST - S. (NIM : 150 30 120), Rivai
Abstract: Piles are structure members that are made from steel, concrete, or timber. They used to build pile foundations, which are deep and which cost more than shallow foundation. Despite the pile foundations cost more expensive, the used of pile to ensure structural in conditions safety. Vesic in the year 1977 identified some condition that requires pile foundations: 1. When Upper soil layer more compressible and too weak to support the load transmitted by upper structure, shallow foundation cannot reach soil more stronger than upper layer so pile foundation can reach more stronger soil layer and can reach bedrock. 2. When upper structure must have resist horizontal forced, pile foundations resist by bending while still supporting the vertical load transmitted by upper structure. This type of situations is generally encountered in the design and constructions of earth retaining structure and foundations of tall structure that are subjected of high wind or earthquake forced 3. Some case on expansive soils may be present at the site of proposed structure; these soils may extend to a great depth below the ground surfaces. Expansive soil swell and shrink as moistures water contents increase and decrease, and the swelling pressure of such soils can be considerable. If shallow foundations are used in such circumstances, the structure may suffer considerable damage. However pile foundations may be considered as an alternative when pile are extended beyond an active zone, which swells and shrinks. 4. Foundations of some structures such as transmission towers, offshore platforms and basement mats below the water table, are subjected to uplifting forces. Piles are sometimes used for these foundations to resist the uplifting forces by wind or wave. 5. Bridge abutment and pier usually constructed over pile foundations to avoid the possible loss of bearing capacity that a shallow foundations might suffer because of soil erosion at the ground surfaces.